Criminal Sanctions for the Sale of Human Organs Under Article 124 Paragraph 3 of Law Number 17 of 2023 on Health - Muhammad Zulfikri Mustakim; Enceng Arif Faizal; Didi Sumardi (Fakultas Agama Islam, 2026)
Human organ trafficking is a form of crime that contradicts humanitarian principles, positive law, and Islamic values. As an evolving criminal phenomenon, this offense requires a comprehensive legal analysis, including from the perspective of Islamic criminal law. This study aims to analyze the constituent elements of the crime of human organ trafficking and examine the classification of sanctions applicable under Islamic criminal law. The research employs a normative juridical method using both statutory and conceptual approaches. Data were collected through a library research method encompassing legislation, legal literature, scholarly journals, and other relevant sources, which were subsequently analyzed using a descriptive-analytical technique. The findings indicate that human organ trafficking fulfills the elements of criminal liability and, from the perspective of Islamic criminal law, is classified as jarimah taʿzir because no specific sanction for this offense is explicitly prescribed in the Qur’an or Hadith. Furthermore, the study finds that sanctions imposed on offenders may be classified according to the consequences arising from the offense, namely taʿzir, qisās-diyāt, or hudūd, when the crime is accompanied by other offenses that satisfy the legal elements of each respective jarimah. These findings demonstrate the flexibility of Islamic criminal law in responding to the development of contemporary forms of crime.